Magnetohydrodynamic time-dependent computational natural convection flow, heat and mass transfer in inclined semi-circular enclosures - Rahman, M. M.; Öztop, Hakan Fehmi; Saidur, R.; Naim, A. G.; Al-Salem, Khaled S.; Ibrahim, Talaat A. (Emerald Group Publishing Ltd, 2016)
Purpose - The purpose of this paper is to make a numerical analysis on unsteady analysis of natural convection heat and mass transfer to obtain flow field, temperature distribution, and concentration distribution. Design/methodology/approach - A finite element method is applied to solve governing equations of natural convection in curvilinear-shaped system for different parameters as thermal Rayleigh numbers (103 = RaT = 106), inclination angle (0 degrees = phi = 60 degrees) and Hartmann numbers (0 = Ha = 100). Findings - Both magnetic field and inclination angle can be used as control parameter on heat and mass transfer. Flow strength decreases almost 100 percent between Ha = 0 and Ha = 100 on behalf of the higher values of thermal Rayleigh number. Originality/value - The originality of this work is to application of magnetic field on time-dependent natural convection flow, heat and mass transfer for curvilinear geometry.
Keywords: Natural convection; Heat transfer; Unsteady; Mass transfer; Enclosure; Semi-circular